PoPA - Sharps: A new framework for cost-effective design of hybrid power systems - Rozali, N.E.M. (Italian Association of Chemical Engineering - AIDIC, 2017)
Development of Power Pinch Analysis (PoPA) for the design and optimisation of Hybrid Power Systems (HPS) is steadily progressing. Even though PoPA has been developed for widespread applications in HPS design analysis, the economic aspect still needs more attention. This work presents a new framework for the design of a cost-effective HPS by incorporating PoPA with a cost-screening tool known as the Systematic Hierarchical Approach for Resilient Process Screening (SHARPS). SHARPS which was originally developed to screen various process changes options in water network is adapted to imbed cost analysis and renewable energy (RE) technology screening in power network. Demonstration on an illustrative case study shows that the proposed framework can provide the best HPS scheme considering the system efficiency, while satisfying the desired payback period. Copyright © 2017, AIDIC Servizi S.r.l..